Coffee bean physical quality: The effect of climate change adaptation behavior of shifting up cultivation area to a higher elevation - SAMSUL BAKRI; AGUS SETIAWAN; IDA NURHAIDA (Society for Indonesian Biodiversity, 2018)
Bakri S, Setiawan A, Nurhaida I. 2018. Coffee bean physical quality: The effect of climate change adaptation behavior of shifting up cultivation area to a higher elevation. Biodiversitas 19: 413-420. The coffee cultivation shifting into a higher elevation can be considered as a farmer’s behavioral adaptation to the climate change to find an optimum temperature and more fertile soil for the coffee growth. The behavior is rampant for Robusta coffee (Coffea canephora) planters in Lampung Province, the main contributor area that places Indonesia as the second largest coffee bean exporting country for more than two decades. The behavior certainly causes environmental deterioration, while the positive impact has not been well-measured, even for physical bean performance that determine its export competitiveness. This study aimed to determine the effect of the behavior on two coffee bean physical indices, the 1000-dried fruit weight or the index of [W_1000], and the percentage of floated fruit upon water soaking or the index of [FLOAT]. Ordinary Least Square Model was applied at a significance level of 10% with the two indices as the response variables. The predictor variable is the elevation area, accompanied by slope steepness and area position in relation to its exposure against solar radiation. The field survey lasted from June to August 2017. Riped coffee fruit samples were collected from 32 sites, ranging from 300 to 1,170 m asl. The results suggested that the behavior would improve the [W_1000] index but worsening the other.